Optimization of Creative Economy-Based Digital Content to Enhance the Competitiveness of Villa Uma Sapna Bali - Liliyan, Aditya; Danang Dwi Saputro (Bulletin of Management and Business, 2025)
Digital transformation has revolutionized how tourism destinations interact with travelers, particularly through creative digital content distributed across various online platforms. This study aims to analyze the influence of creative digital content, storytelling, and content personalization on destination competitiveness, with a case study at Villa Uma Sapna Bali. A quantitative causal-associative approach was used, involving 160 respondents who had interacted with the villa’s digital content through social media. Data were collected via an online questionnaire and analyzed using multiple linear regression with SPSS software. The results show that creative digital content does not have a significant effect on destination competitiveness (Sig. = 0.716 > 0.05), while storytelling and content personalization have a positive and significant effect (Sig. = 0.000 < 0.05). These findings highlight that digital marketing strategies emphasizing emotional narratives, personal engagement, and cultural representation are more effective in strengthening the competitiveness of tourism destinations than those relying solely on visual creativity. Theoretically, this study contributes to the development of creative economy-based digital marketing concepts, while practically, it provides guidance for tourism managers to design narrative-driven and personalized digital content to achieve sustainable destination competitiveness.